SOME ASPECTS OF BIOLOGY OF THE WHITE-SPOTTED SPINE-FOOT, SIGANUS CANALICULATUS (PARK, 1797) FROM THE GULF OF MANNAR - Jayasankar, P (Indian Journal of Fisheries, 2011)
Siganids are excellent food fishes having great mariculture potential and some information on the biology of this group is available (Lam, 1974; Hasse et al, 1977). Works on siganids from Indian v/aters are scanty, being restricted to that of traditional trap fishery (Mohan, 1985), food and feeding (Balasubramanyam and Natarajan, 1980), taxonomy (Pius, 1984) and length-weight relationship (Lazarus and Reddy, 1986-’87). The present study deals with length-weight relationship, maturation and spawning of S. canaliculatus from Keelakarai (Gulf of Mannar). MATERIAL